Relationship of Salmonella infection and inflammatory intestinal response with hematological and serum biochemical values in laying hens - Soria, Mario; Bonnet, María Agustina; Bueno, Dante Javier (2017)
There are few studies about the blood serum of laying hens infected with Salmonella. The differential leukocyte count and blood chemistry values are an important aid in the diagnosis of human diseases, but blood parameters in the avian species are not well known. On the other hand, invasive forms of bacterial gastroenteritis, like Salmonella, often cause intestinal inflammation so this study was undertaken to find a biomarker of Salmonella infection and inflammatory intestinal response in the hematological or serum biochemical parameters in laying hens. Furthermore, we evaluated the association of some farm characteristics with Salmonella infection and fecal leukocytes (FL). A fecal sample with at least one fecal leukocyte per field was considered positive for inflammatory intestinal response. False positive serum reactions for Salmonella infection, by serum plate agglutination (SPA) test, were reduced by heating the sample to 56 °C for 30 min and then diluting it 5-fold. The range of hematological and biochemical parameter values was very wide, in addition, there was a poor agreement between the SPA and FL results. Comparison of the positive and negative samples in SPA and FL showed that 1.3% and 79.8% of the laying hens were positive and negative in both tests, respectively. Hens with a positive SPA result showed a higher percentage of monocytes than those with a negative SPA result. Hens with a positive FL test had a higher percentage of heterophils, ratio of heterophils to lymphocytes and aspartate aminotransferase values, while the percentage of lymphocytes was significantly lower (P < 0.05) than those with a negative FL test. The risk of Salmonella infection increased when the age of laying hens and the number of hens per poultry house was greater than or equal to 18 months old and 10,000 laying hens, compared to less than 18 months old and 10,000 laying hens, respectively. On the other hand, the risk of inflammatory intestinal response was higher in laying hens ≥18 months old than in hens <18 months old. Despite the fact that we did not find any specific biomarker of Salmonella infection, this is the first report about the change of Salmonella infection and inflammatory response in hematological/serum biochemical values for laying hens.